Mobility (1997)
The various techniques of stretching may be grouped as Static, Ballistic and Assisted. In both Static and Ballistic exercises the athlete is in control of the movements. In Assisted the movement is controlled by an external force which is usually a partner. Mobility Exercise Programme are descripted.